Determinan Praktik Perataan Laba - Barbara Gunawan; Anggarapindo Hardjunanto (Universitas Kristen Maranatha, 2020)
The purpose of this study was to determine the factors that influence the practice of income smoothing in manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2017 period.This research used a purposive sampling method to determine the sample according to the criteria needed in the research. Thus, it is got 34 company samples and can process 136 companies. The analyzer of this research used logistic regression.The results showed that the effect of profitability, company size, financial leverage, firm value on income smoothing practices has no effect, while dividend payout ratio variable proved to have a significant positive effect on income smoothing practices, and Institutional ownership variable proved to have a significant negative effect on income smoothing practices Keywords: Profitability, Company Size, Financial Leverage, Firm Value, Dividend Payout Ratio, and Institutional Ownership